Alternative strategies for mitigating global warming through the application of rice straw waste composting technology - Muliarta I. Nengah (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The purpose of this article is to determine the composting method of rice straw waste that is adaptive to global warming mitigation efforts. Two composting methods are commonly known as innovations in rice straw waste management, namely aerobic and anaerobic, but no one has studied methods that are in line with global warming mitigation.